Changing Dimensions in the Menace of Cyber Crime; a Contemporary Situational Analysis - Prayaga M.A* (International Journal of Advanced Science and Technology, 2020)
Process of globalization furnished the entire planet into a more considerable vend where the matter of inventiveness is under the grip of dearth. The Pertaining state of affairs urges every authority to supplant its subsisting mechanism accordingly. Unanticipated upsurge in the figure of crimes related to cyber field need to be affixed with the pace of the effect of globalization mechanisms. Put it differently, the forces that have precipitated the global march of this phenomenon are the selfsame inclusive conditions that laid the stone for the absolute widening of e-crime. These conditions can be figured as unregulated interdependence, digital connectivity and deterritorialization that contain the manifold occurrence of cybercrime. It is quite pertinent to regard this menace from the lens of socio discursive standpoint in order to balance the social order of this era. In this paper an attempt has been made to scrutinize the impact of globalization and effect of after days on the cybercrime and some suggestions have been made for the need of changes in our administrative mechanism to cope up with the octopian spread of this menace.